2005
DOI: 10.1021/ma047947w
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Luminescent Properties of Fluorene Copolymers Bearing DCM Pendants

Abstract: A series of copolymers, poly [(9,9-dioctylfluorene-2,7-diyl)-co-(4-dicyanomethylene-2-methyl-6-[4-(diphenylamino)styryl]-4H-pyran-4′,4′′-diyl)], were synthesized by polymerizing 2,7-bis(4,4,5,5tetramethyl-1,3,2-dioxaborolan-2-yl)-9,9-dioctylfluorene with mixtures of 2,7-dibromo-9,9-dioctylfluorene and 4-dicyanomethylene-2-methyl-6-[bis(4′-bromophenyl)amino]styryl]-4H-pyran (a DCM derivative) by the palladium-catalyzed Suzuki coupling reaction. The copolymers were characterized by molecular weight determination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 73 publications
1
22
0
Order By: Relevance
“…[19] New derivatives of DCM for device applications were published by Jung et al [20] Jin and coworkers reported the synthesis and luminescent properties of fluorene copolymers bearing DCM pendants. [21] Recently, Choi and co-workers reported the red-emitting phenothiazine dendrimers encapsulated with DCM derivatives. [22] So far, light harvesting molecule of pyrene/DCM combination has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[19] New derivatives of DCM for device applications were published by Jung et al [20] Jin and coworkers reported the synthesis and luminescent properties of fluorene copolymers bearing DCM pendants. [21] Recently, Choi and co-workers reported the red-emitting phenothiazine dendrimers encapsulated with DCM derivatives. [22] So far, light harvesting molecule of pyrene/DCM combination has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The thermal decomposition temperature ( T d ) and glass transition temperature ( T g ) of P1 is 406 °C (∼5% loss) and 145 °C, as examined by thermogravimetric analysis (TGA) and differential scanning calorimeter (DSC). The T g of P1 is much higher than 97 °C for poly(9,9‐dioctylfluorene) (PFO) 42. The high T g is conducive to reducing crystallization and to retaining long‐term morphological stability when applied as an active layer in EL devices 43…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, green light from BT units was also observed. [126]. In solid state, only a long-wavelength emission at 620 nm originating from the DCM moieties is observed.…”
Section: Green-light-emitting Polyfluorene Derivativesmentioning
confidence: 93%